Analisis Perbandingan Risiko Pembiayaan Murabahah dan Mudharabah Baitul Maal - Nur Rochmah, Eva; Fitriyani, Yeny; Purwanto (ARBITRASE: Journal of Economics and Accounting, 2024)
This research compares murabahah and mudharabah financing risks at the Baitul Maal wat Tamwil (BMT) Tumang Tegalrejo Branch. This research aims to understand the risks associated with both financing models in microfinance institutions. Qualitative methods are used to answer research objectives. Research data was collected through direct interviews with BMT Tumang Tegalrejo Branch managers so that researchers could get a direct view of the risks faced in murabahah and mudharabah financing. Data analysis uses descriptive analysis techniques. The results of the analysis provide evidence of differences in risk between the murabahah and mudharabah financing models. Understanding the risks of Sharia financing can provide a strong basis for developing risk management strategies that are more effective in providing such an important contribution. This research enriches the literature on risks in Sharia microfinance financing institutions.